A self-adjusting, progressive shock strength procedure to investigate resistance to punishment: Characterization in male and female rats. (1st December 2022) - Desmercieres, Stevenson; Lardeux, Virginie; Longueville, Jean-Emmanuel; Hanna, Myriam; Panlilio, Leigh V.; Thiriet, Nathalie; Solinas, Marcello
Abstract: Indifference to harmful consequences is one of the main characteristics of compulsive behaviors and addiction. Animal models that provide a rapid and effective measure of resistance to punishment could be critical for the investigation of mechanisms underlying these maladaptive behaviors. Here, analogous to the progressive ratio (PR) procedure widely used to evaluate appetitive motivation as the response requirement is increased, we developed a self-adjusting, progressive shock strength (PSS) procedure. The PSS provides, within a single session, a break point that quantifies the propensity to work for a reward in spite of receiving electric footshock that progressively increases in duration. In both male and female rats, the PSS break point was sensitive to 1) hunger; and 2) changes in the qualitative, but not quantitative, incentive value of the reward. In systematic comparisons between PSS and PR procedures in the same rats, we found that both measures are sensitive to manipulations of motivational states, but they are not intercorrelated, suggesting that they measure overlapping but partially distinct processes. Importantly, the PSS procedure represents a refinement in the 3Rs principles of animal research because animals can control the strength of shock that they are willing to tolerate. This self-adjusting PSS procedure may represent a useful tool to investigate mechanisms underlying maladaptive behavior that persists in certain individuals despite harmful consequences. Highlights: In the PSS the strenght of shock is adjusted according to the animal's behavior. Animals can titrate the level of punishment they would tolerate to obtain a reward. PSS break points are sensitive to manipulations of motivation in males and females. The PSS and progressive ratio break points are not correlated. The PSS represents a form of refinement in the 3Rs principles of animal research.